Pembangunan Ketahanan Keluarga Berdasarkan Peraturan Daerah Kota Tangerang Nomor 1 Tahun 2019; Studi Analisis Kebijakan - Ririn Marina Oktavia (Epistemik: Indonesian Journal of Social and Political Science, 2020)
Family resilience is a description of the family's ability to meet all family needs related to basic needs. This study aims to explain the policies taken by the Tangerang city government and the Tangerang City DPRD in order to improve the development of family resilience. This study uses a qualitative type of research by paying attention to and seeing what is behind the formation of the Tangerang city regional regulation number 1 of 2019 regarding the development of family resilience and finding out the extent of the socialization process. Data collection techniques using the interview method. The analysis used in this research is descriptive. The results of this study can be seen from Perda number 1 of 2019 concerning the development of family resilience, including physical resilience, economic resilience, social-psychological resilience, and socio-cultural resilience. In this study, researchers chose the object of economic resilience as the main research.